At Your Service! The Role of Tax Havens in International Trade with Services - Shafik Hebous; Niels Johannesen (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper documents that tax havens play a prominent role in international service trade and investigates the nature of this role. We employ a firm-level dataset with detailed information about service trade and foreign affiliates for virtually all multinational firms in Germany, which allows us to approximately distinguish trade between related and unrelated parties. We find that the service trade of tax havens partly reflects genuine specialization in service industries, which suggests that institutional features such as low tax rates, secrecy and low regulatory standards create a comparative advantage in service production. We also find that trade in service categories such as intellectual property (patents and trademarks) and headquarter services (administration, management and advertising) partly reflects mispriced affiliate trade serving to shift profits to tax havens. We argue, however, that the loss of government revenue resulting from this type of corporate tax evasion is likely to be modest.
Keywords: F14; F23; H26; 330; service trade; profit shifting; tax evasion; multinational firms; tax havens